Operational efficiency of bank loans and deposits: A case study of Vietnamese banking system - Tram Nguyen; David Tripe; Ngo Thanh (International Journal of Financial Studies, 2018)
This paper examines whether there is a causal relationship between bank loans and deposits in the Vietnamese banking system and the efficiency of the use of loans and deposits by the Vietnamese banks. In a country such as Vietnam, where inter-bank money markets are relatively underdeveloped, one would expect a reasonably strong relationship between deposits and loans. A pooled cross-sectional sample of financial ratios is collected from annual reports of 44 Vietnamese banks covering the period 2008-2015. The explanatory power of instrumental variables in relation to the endogenous variables is tested. A deterministic frontier model based on corrected ordinary least squares, estimated by three-stage least squares on a simultaneous equations model, is employed to derive the frontiers for the sampled banks as well as to estimate the causality between bank loans and deposits. Our findings suggest that, in an underdeveloped banking system such as Vietnam, bank deposits have a positive and significant impact on bank loans, but the reverse relationship is not significant. It is further suggested that in deposit-taking and loan-creating activities, Vietnamese banks performed moderately well over the period examined; however, in the near future, they should start to focus more on deposit-taking activities.
Keywords: C1; C30; G21; 330; simultaneous equations model (SEM); corrected ordinary least squares (COLS); three-stage least squares (3SLS); causality; loans; deposits; Vietnamese banks